The Changing Face of Economics? Ethical Issues in Contemporary Economic Schools as a Consequence of Changes in the Concept of Human Nature - Horodecka, Anna (Annales. Etyka w Życiu Gospodarczym, 2015)
The last financial crisis combined with some recent social trends (like growing inequality or environmental problems) inspired many contemporary economists to there-evaluation of actual economic knowledge in the search for solutions to theseproblems. Modern economic schools (especially heterodox ones) stress the meaningof ethical issues in economics more often. The thesis of the paper is that this revivalof the ethical face of present economics depends very strongly on the changing assumptions of human nature within economics and other disciplines which workalongside economics, such as social psychology or business ethics, for instance. Inorder to prove the thesis, the paper provides an evaluation of current economicschools, especially within the heterodoxy, in search of their ethical aspects, and presents them as a result of the changing assumptions about human beings within thoseschools. This ethical dimension of human beings manifests itself in different ways,which can be perceived as a result of it being based on different ethical schools anddifferent psychological and philosophical assumptions about human nature. Therefore, the paper also considers the current developments of the view on human beingsin contemporary schools of economic ethics.